Reimagining entrepreneurship: A post-individualist philosophical inquiry into identity, ethics, and agency - Paudel, Ram; Titov, Eneken; Shrestha, Laba Kumar (Privietlab, 2023)
Entrepreneurship has always been interpreted as a pattern that presupposes self-autonomy, economic rationality, and market-driven innovation. However, these pillars are eroded by the recent socio-cultural changes which are marked by the increasing collectivism, ethical pluralism, and technologically mediated changes. The current conceptual argument is a reconceptualization of entrepreneurship post-individualism that incorporates elements of existential, communitarian and ethical tradition based on the thinkers like Heidegger, Arendt and Bauman. Being based on philosophical hermeneutics, the paper criticizes liberal individualist model and reorients entrepreneurial identity as a process that occurs as a socially embedded and ethically driven process. Its main themes are how it seems to be a conflict between individuality and normative behavior, the decreasing of authenticity in the entrepreneurial culture, and how networks, technology and collective action are transformative. Through combining the knowledge of sociology, political economy and innovation theory, the paper suggests a comprehensive interpretation of entrepreneurship that put an emphasis on the relevance of significance, relations and the cultural sustainability rather than on the profitability and simple economic production. Entrepreneurship education, policy frameworks and ecosystem design are all implicated and it is argued that approaches that would enhance ethical responsibility, social interdependence, and collaborative agency in the entrepreneurship ecosystem should be encouraged. The piece will also be of use to fledgling interdisciplinary discussions, providing as it does a normative and ontological reconfiguration of entrepreneurship that will be suited to post-modern, digitally networked societies.